A comparison of four styles of racing start in swimming - Ayalon, A.; van Gheluwe, B.; Kanitz, M. (Swimming II: Proceedings of the Second International Symposium on Biomechanics in Swimming, Brussels, Belgium, 1975)
The purpose of this study was to compare four styles of swimming racing starts: 1) the conventional style (straight backswing), 2) the grab start, 3) the bunch start, and 4) the track start. The track start was similar to the bunch start except that in the track start support for the back leg was provided while the hands were on the block.